Imagining Images. Seven Problems - Elkins, James (img journal, 2019)
The following text is the transcript of the keynote held at the IMG2017 conference at the Facolty of Education of the Free University of Bozen, on November 27, 2017 in Brixen campus, on a video plenary session. Seven problems are presented to define some stable points and some perspective to outline a theory of images. The seven problems are: 1. Why it may be a good thing that few people know what image is. 2. What is not an image? 3. Aesthetics and politics. 4. Do images have a nature? 5. The madness of cassifying images. 6. The limits of scholarships’ attention to detail. 7. The materiality of image.